O etnoconhecimento no processo de maturação da banana (Musa SPP) utilizado por agricultores familiares da comunidade do Itacupé, Abaetetuba-PA - MAC-DOVEL, Jéssica Moraes (2019)
Banana cultivation is a formidable crop, especially for the rural population, since the banana fruit (Musa spp) is an important source of food, including continuous fruit, being a fruit produced all year round, as well as being a source of employment and income, thus keeping the man in the field. A common practice in many communities to accelerate the ripening of bananas is the use of raffia bags wrapped around the fruit bunch. Although it is a common practice in many communities, they are still unaware of the chemical and biological processes responsible for such phenomena. In this way, the research aims to find out about the ethnoconference that the farmers have on the process of accelerating the ripening of the banana fruits wrapped in raffia bags and compare with the scientific knowledge involved in the maturation process. Therefore, in order to verify this process, it was decided to carry out a field research in the community of Itacupé, belonging to the municipality of Abaetetuba, with a semi-structured qualitative / quantitative interview in order to reach the objectives of the present study. The research is based on authors such as: Marcos André de Souza Prill, Leandro Camargo Neves, Jéssica Milanez Tosin, Edvan Alves Chagas, Cynthia Ditchfield and Carmen C. Tadini. Therefore, it was possible to infer that the one responsible for the maturation of fruits, especially the banana, is the ethene gas (ethylene), which acts as a hormone synthesized in the cells and present in all parts of the fruit, when this gas is released triggers three processes , lipid oxidation (breaking of the banana fibers, making it soft), breakage of the starch bindings (responsible for the sweetness of the fruit) and breaking of the chlorophyll molecules (responsible for the change in color from green to yellow). The ripening of the banana is accelerated when placed in raffia bags, because this entrap the ethylene released by the fruit, thus a high concentration of this gas is in the inner part of the container, which according to the concepts of chemical kinetics increases the speed of maturation.